Fluorescence advanced videodermoscopy: a new method of hairs and scalp evaluation. Comparison with trichoscopy. (17th August 2021) - Rossi, A.; Magri, F.; Caro, G.; Michelini, S.; Di Fraia, M.; Fortuna, M.C.; Pellacani, G.; Carlesimo, M.
Abstract: Introduction: Non‐invasive diagnostic methods in clinical dermatology are widely used to reduce the need for invasive techniques, with great advantages in terms of cost and time. Dermoscopy is the reference test for the in vivo diagnosis of cutaneous lesions, and when it is performed on the scalp region it is named trichoscopy. Fluorescence advanced videodermoscopy (FAV) has been lately proposed as a new non‐invasive method for the in vivo skin examination at high magnification, with cell‐level resolution. So far, it has shown promising results for the assessment of melanocytic and vascular lesions and for the in vivo diagnosis of parasitosis. Objectives: This observational study aims to perform, for the first time, a morphologic study of healthy scalp and scalp elementary lesions using FAV and to compare it with trichoscopy. Methods: We enrolled 90 healthy individuals for the evaluation of the scalp using FAV. Then, we recruited 53 patients with alopecia and collected images of the elementary lesions using FAV and trichoscopy. Results: Three hundred healthy scalp FAV images of different epidermal layers, papillary dermis, follicular ostia and healthy hair shafts were collected. Three hundred and eighty FAV and trichoscopic images of alopecic scalp elementary lesions were collected, showing that FAV provided a more detailed observation than trichoscopy, with higher magnification and cellular resolution. Conclusion: Fluorescence advanced videodermoscopy may represent a new valid technique of support to trichoscopy, adding further information, increasing chances of diagnosis and decreasing the need of invasive procedures.